NEUROSCIENCE AND THE LEARNING STAGES OF SANTRI: THE TRADITION OF QUR’AN MEMORIZATION IN ISLAMIC EDUCATION - Khasnah Syaidah; Ainurrafiq Dawam; Nur Afif; Ellys Lestari Pambayun (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
The tradition of Quranic memorization in pesantren has lasted for centuries, but has not been extensively studied from a neuroscience perspective to understand the learning mechanisms of students' brains. Pesantren face challenges in optimizing the effectiveness of memorization learning, especially for students with diverse abilities, including slow learners. This research aims to analyze the integration of neuroscience in the Quranic memorization tradition, examine the relevance of traditional methods with brain working principles, and formulate recommendations for neuroscience-based learning development. The research employs library research methods with an interdisciplinary qualitative approach that integrates neuroscience, Islamic education, and pesantren studies perspectives. Data were collected through documentary studies of primary and secondary literature, analyzed descriptively, comparatively, and synthetically with source triangulation. Research findings show that traditional memorization methods such as tikrar, tallaqi, murajaah, and wahdah have strong neurobiological foundations aligned with neuroplasticity principles, spaced repetition, and social learning. Neuroscience integration optimizes student learning stages through right, left, and middle brain activation, as well as learning strategies based on visualization, association, and motivation. This approach is effective for various student characteristics, including implementation of tasmi', kitabah, and hypno-motivation methods for slow learners, contributing to improved tahfidz learning effectiveness in contemporary Islamic education.